2010
DOI: 10.1093/jac/dkq200
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes with daptomycin in the treatment of Staphylococcus aureus infections with a range of vancomycin MICs

Abstract: ObjectivesRecent recommendations by the Infectious Diseases Society of America for the treatment of Staphylococcus aureus suggest the use of alternative agents when vancomycin MIC values are ≥2 mg/L. This study examines the outcome of patients treated with daptomycin for S. aureus infections with documented vancomycin MICs.Patients and methodsAll patients with skin, bacteraemia and endocarditis infections due to S. aureus with vancomycin MIC values in CORE 2005–08, a retrospective, multicentre, observational r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Clinical outcomes and mortality are shown in Table 1 The optimum alternative treatment regimen for MRSA bacteraemia with higher vancomycin MICs is still unclear. As reported previously, daptomycin is non-inferior to vancomycin in patients with bacteraemia, infective endocarditis and complicated skin and skin-structure infections caused by MRSA [4,5]. However, these studies included a diverse disease spectrum with or without bacteraemia, a broad range of vancomycin MICs and non-strict definitions for daptomycin therapy.…”
Section: Sirmentioning
confidence: 99%
“…Clinical outcomes and mortality are shown in Table 1 The optimum alternative treatment regimen for MRSA bacteraemia with higher vancomycin MICs is still unclear. As reported previously, daptomycin is non-inferior to vancomycin in patients with bacteraemia, infective endocarditis and complicated skin and skin-structure infections caused by MRSA [4,5]. However, these studies included a diverse disease spectrum with or without bacteraemia, a broad range of vancomycin MICs and non-strict definitions for daptomycin therapy.…”
Section: Sirmentioning
confidence: 99%
“…Some studies have shown no significant association between higher MICs and poor outcomes, 7,8 but others have suggested an association with increased treatment failures and higher mortality. 9-13 Unfortunately, there are many differences in variables between individual studies (different patient populations, laboratory methods, outcome measures, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Weston et al reported higher clinical failure rates among vancomycin-treated patients than daptomycin-treated patients (51.0% versus 34.0%; P ϭ 0.048) and noted that the outcomes did not change in those treated with daptomycin, regardless of renal function (16). Currently, there are few studies that have directly addressed the impact of elevated vancomycin MICs on patient outcomes when patients are treated with daptomycin for MRSA BSIs and the current literature has failed to demonstrate the same association between outcomes and elevated MIC as with vancomycin-treated patients, making daptomycin an ideal treatment alternative (17).…”
mentioning
confidence: 99%